Patentes: experiencias de éxito - Contreras Cossio, Jorge (2021)
Jorge Contreras Cossio (Perú) - Expositor / Silvana Flores Chávez (Perú)- Expositora / Eduardo Roberto Fernández (Argentina)- Expositor